2003
DOI: 10.1142/s0218271803003451
|View full text |Cite
|
Sign up to set email alerts
|

THE OPTICAL-X-RAY–GAMMA-RAY SPECTRAL ENERGY DISTRIBUTIONS OF GEV GAMMA-RAY LOUD BLAZARS AND CONNECTION AMONG LBLs, HBLs AND FSRQs

Abstract: In this paper, we introduce a new composite spectral indices αγxγ = αxγ - αγ, and prove [Formula: see text], that means αγxγ is intrinsic. We plot a αxox - αγxγ diagram for 25 Gev γ-ray blazars for which αx and αγ have been provided in the literature, where αxox = αox - αx which was introduced by Sambruna et al. (1996) and proved that it is intrinsic by our previous paper (Xie et al. 2001). Using this new composite color–color (αxox - αγxγ) diagram, we investigated the nature of the HBLs–LBLs relationship, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
12
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 18 publications
16
12
0
Order By: Relevance
“…This similar trend was also obtained by other authors (e.g. Xie et al, 2003;Sambruna et al, 1996;Ghisellini et al, 1998;Böttcher & Dermer, 2002;Maraschi et al, 2008) who found that similar physical processes operate in three kinds of blazars. However, Antón & Browne (2005) found that there are selection effects for the "blazars sequence".…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This similar trend was also obtained by other authors (e.g. Xie et al, 2003;Sambruna et al, 1996;Ghisellini et al, 1998;Böttcher & Dermer, 2002;Maraschi et al, 2008) who found that similar physical processes operate in three kinds of blazars. However, Antón & Browne (2005) found that there are selection effects for the "blazars sequence".…”
Section: Discussionsupporting
confidence: 91%
“…Chen et al, 2013;Fan et al, 2012;Li et al, 2010;Lyu et al, 2014;Xie et al, 2003). This suggests that FSRQs and LBLs have a similar property, but HBLs have a distinct property.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Basing on that blazars show rapid flux variations on a timescale of hours in the optical band and even minutes in the high energy gamma-ray band (e.g., Gaidos et al 1996;Mattox et al 1997;Xie et al 2002;Aleksić et al 2011;Arlen et al 2013), Chiaro et al (2016 accessed the type of a BCU by comparing its flaring pattern in the gamma-ray band with that of BL Lacs and FSRQs. It was found that BL Lacs and FSRQs are distributed in different regions in some planes of broadband spectral indices (Padovani & Giommi 1995;Sambruna et al 1996;Xie et al 2003;Li et al 2015). Padovani & Giommi (1995) showed that HBLs and LBLs are distributed in different regions in the α ro -α ox plane, where α ro and α ox are broadband spectral indices in the radio, optical, and X-ray bands.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, searching for connections between the different types of blazars, namely, HBLs, LBLs and FSRQs, will substantially advance our understanding of the fundamental nature of blazars. This topic has been studied by many authors (Padovani & Giommi 1995;Giommi et al 1990;Lamer, Brunner & Staubert 1996;Sambruna et al 1996;Stecker et al 1996;Wolter, Comastri & Ghisellini 1998;Xie et al 2001aXie et al , 2001bXie et al , 2003Xie et al , 2004cD'Elia & Cavalitre 2001;Böttcher & Dermer 2002). The properties of LBLs are systematically different from those of HBLs: (1) These two subclasses occupy different regions on the α ro − α ox plane, which shows the indicative spectral energy distribution; (2) There exist correlations between the minimum soft X-ray flux and radio flux, and between the radio and optical fluxes for HBLs, but not for LBLs; (3) The observed peak of emitted power typically locates at millimeter/IR for LBLs and at UV/soft X-ray wavelength for HBLs; (4) FSRQs, HBLs and LBLs are mixed together in the α ox -α xγ plane but are located in separate regions in the diagram of composite spectral indices α xox -α γxγ .…”
Section: Introductionmentioning
confidence: 99%